PEMAHAMAN MANASIK HAJI DI KALANGAN PERSIS PERSPEKTIF LIVING HADIS - Agung Danarta; Indal Abror (Indonesian Journal of Islamic Literature and Muslim Society, 2018)
This study aims to examine the meaning of the hadith about "take from me mansik of Hajj" among the PERSIS. The issue that is the focus of this research is a problem related to the pilgrimage ritual problem that is understood by a group of community organizations known as Islamic Unity (PERSIS). This research will be limited to the study of living hadith. This term can be defined as a phenomenon in the form of behavior patterns in Islamic societies that arise from their understanding of the hadith. The results showed that understanding Hajj rituals for PERSIS was important. This can be seen from the importance of the example of the Prophet Muhammad. Among pilgrims, there are those who make it important so that in carrying out the Hajj and its rituals must be in accordance with what is exemplified by the Prophet Muhammad. The importance of Hajj management changes that can make the pilgrimage run comfortably, and they can go home safely and healthily. So that after returning home can actualize in daily worship activities better